PRINSIP DEMOKRASI DAN NOMOKRASI DI DALAM UUD RI 1945 PASCA AMANDEMEN DAN IMPLEMENASINYA DALAM STRUKTUR KETATANEGARAAN REPUBLIK INDONESIA - M. Muslih (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
The spirit redistribute the power of the state in the 1945 Constitution after the amendment embody two major power balance. Each is the power of the people (democracy) and the rule of law (nomocracy). On the one hand, the 1945 Constitution established social ideals Indonesia to realize the power of the people as the "owner" of the original state. While on the other side, the 1945 Constitution also gives the place the rule of law. Configure both show the face of hegemony and domination dom, but when examined more closely essensinya is giving reinforcement. Indonesia's social goal is to realize the essence of a democratic state based on the rule of law. In such characteristics, the structure of the constitution is not qualified as a holder of hegemonic power. He is actually more as a "container" of the state power distribution.Keyword :  Principle, democracy, constitutional